Abstract Book VI Congress of Mexican Ozone Therapy (Ozone Therapy Global Journal, 2019)
VI Congreso de la Sociedad Mexicana de Ozono TerapiaVI Congress of Mexican Ozone Therapy Association (AMOZON)Cancún, México, 17- 19 noviembre 2018.“Empoderando la Ozono Terapia en la Ciencia y El Servicio””Supporting the Scientific Bases and Applicability of Ozone Therapy”Abstract Book / Resúmenes